Comparative immediate effect of different yoga asanas on heart rate and blood pressure in healthy young volunteers - Bhavanani, Ananda Balayogi (Medknow Publications & Media Pvt Ltd, 2014)
INTRODUCTION: This study planned to compare immediate cardiovascular effects of different yoga asanas in healthy young volunteers. MATERIALS AND METHODS: Heart rate (HR), systolic pressure (SP), and diastolic pressure (DP), blood pressure (BP), were recorded using the non invasive blood pressure (NIBP) apparatus in 22 healthy young subjects, before and after the performance of Dhanurasana (DA), Vakrasana (VA) (both sides), Janusirasasana (JSA) (both sides), Matsyasana and Shavasana for 30 s. HR and BP were further recorded during supine recovery at 2, 4, 6, 8, and 10 min. A repeated measure of ANOVA was used for statistical analysis. RESULTS: There were significant changes in HR and BP both immediately after the Asanas as well as during the recovery period. Overall comparisons of ∆% changes immediately after the performance of the Asanas revealed significant differences with regard to HR that increased significantly after DA. In the recovery phase, there were significant intergroup differences from 2 min onward in both SP and DP. The decrease of SP after VA (right side) (VA-R) was significantly greater than Shavasana (4(th), 6(th), and 8(th) min) and JSA (left side) (JSA-L) at 6(th) and 8(th) min. DP decreased significantly after performing JSA-L compared to VA-R at the 6(th) and 8(th) min. DISCUSSION: The cardiovascular changes immediately after the Asanas and during the recovery phase reveal inherent differences between the selected postures. The rise of HR in DA may be attributed to increased sympathetic response due to the relative difficulty of the posture as well as abdominal compression occurring in it. The effect of supine relaxation is more pronounced after the performance of the Asanas as compared to mere relaxation in Shavasana. This may be attributed to a normalization and resultant homeostatic effect occurring due to a greater, healthier de-activation of the autonomic nervous system occurring towing to the presence of prior activation. There were also subtle differences between the right sided and left sided performance of VA and JSA that may be occurring due to the different internal structures being either compressed or relaxed on either side. CONCLUSION: Our study provides initial evidence of differential cardiovascular effects of Asanas and subtle differences between right and left sided performance. Further, cardiovascular recovery is greater after the performance of the Asanas as compared to shavasan; thus, implying a better response when effort precedes relaxation.